A History of Christian Conversion. By David W. Kling. Oxford: Oxford University Press, 2020. xvi + 836 pp. $150.00. - Levering, Matthew (Horizons, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966922000251/resource/name/firstPage-S0360966922000251a.jpg